A prospective cohort study of digital cushion and corium thickness, Part 2: does thinning of the digital cushion and corium lead to lameness and claw horn disruption lesions? - Newsome, Reuben; Green, Martin J.; Bell, N.J.; Bollard, N.J.; Mason, C.; Whay, H.R.; Huxley, J.N. (American Dairy Science Association, 2017)
The aim of this study was to determine whether a decrease in thickness of the sole soft tissues (SST) beneath the flexor tuberosity of the distal phalanx (i.e. the digital cushion and corium) predisposed a claw to develop claw horn disruption lesions (CHDL) or a leg to lameness. Data were analysed from a longitudinal study of 179 cows, which had been examined at 5 assessment points -8, +1, +9, +17 and +29 weeks relative to either their 1st, 2nd, 3rd or 4th calving. At each assessment point, SST were measured using ultrasonography. Additional assessment point data included sole lesions and back fat thickness (BFT), and cows had been locomotion scored fortnightly from calving. 158 cows completed the study. Separate logistic regression survival analyses were constructed to assess the outcomes, either lameness on a leg or CHDL on a claw; combinations of lameness and lesions were tested as outcomes. Cow level variables tested included farm and lactation number. Variables were tested describing previous SST thickness, minimum previous SST thickness, BFT, and change in either variable between prior assessment points. Prior lesions/lameness strongly predicted repeat cases and the final models had the outcome first lesion or lameness on a claw or leg. In the reported lameness models, lameness was defined as a leg being recorded as lame twice within three consecutive scores, and in the reported lesion models, lesion was defined as the first presence of either a sole ulcer or a severe sole haemorrhage on a claw. Thin SST increased the likelihood of lesion occurrence; thin SST on 43 the lateral claw predicted subsequent lameness on a leg. Thin BFT and thinning of BFT between previous assessment points increased the likelihood of future lesion occurrence. Thin SST and thinning of BFT had additional effects on the likelihood of lesion occurrence, suggesting that BFT and sole SST had independent effects on lesion occurrence. However, change in SST thickness between assessment points did not influenced the likelihood of future lesions or lameness. This suggests that thin SST were not simply a result of depletion of body fat and challenges the theory that thinning of the digital cushion with body fat mobilization leads to CHDL. Other possible mechanisms by which SST become thin are discussed, and could include changes in integrity of the suspensory apparatus with physiological events.